Potential Role of Hospitality Business in Saving Pollinators - Denis VASILIEV (Communications of International Proceedings, 2021)
Pollinator decline is one of the most significant global ecological problems. To address this issue multiple stakeholders need to work in collaboration, and businesses can play an important role here. While link between pollinator decline and agricultural business are straightforward and attracts a lot of attention, the link with hospitality business is often ignored. However, opportunities for the sector contribution to pollinator conservation exist. These opportunities stem from recent growth in popularity of rural tourism, increasing attention to landscape design and sustainability in hospitality sector and growing awareness of customers on ecological issues, including pollinator decline. Integration of hospitality business and pollinator conservation can potentially create synergies that would generate value both for nature protection and for companies. The opportunities are underexplored and therefore are being lost. This, the aim of this article is to highlight areas of potential contribution of hospitality business to pollinator conservation and highlight value that can be generated as  for companies, customers and for nature. A particular attention is paid to integration of pollinator conservation into marketing mix of the companies operating in hospitality business highlighting ecological benefits for pollinators. The study provides recommendations to businesses within the industry. Ideas proposed in present article may have positive implications for both pollinator conservation success and profitability of the industry, ultimately contributing to achievement of the UN Sustainable Development Goals.
Keywords: Sustainable Development; Marketing Mix; Hotel Business.